Rancang bangun pabrik pengamakan kulit sapi untuk tas / koper samak nabati skala kecil - Harniniek, Harniniek; Widowati, Titik Purwati (Majalah Kulit, Karet, dan Plastik, 1987)
This paper is prepared for a design of a small scale vegetable tanning factory, to produce leather for bag or suitcase. The capacity of it will be 22 pieces/day dry cow hides. This factory economical calculations are as follows : the total capital is fixed capital + working capital + Rp 80.196.170,00, the total production cost is variable cost a year + fixed cost a year = Rp 124.479.754,60, variable cost for a year consists of raw material, packing, chemical/supplement material, fuel, electricity and split cost, fixed cost for a year consists of labour salaries, capital interest, maintenance, depreciation and general expences; the manufacturing cost is the total production cost divided by production capacity = Rp 785.86/ sq ft; the profit calculation before taxing is Rp 33.920.245,40, after taxing is Rp 27.136.196,40, the pay out period calculation consists of the percentage of profit to return the capital (rate of return) before taxing is 42.29 %, after taxing is 33.84 % and the pay out period before taxing 2 year 2 months, after taxing 2 years 8 months; the break even calculation consists of the break even point is Rp 66.686.147,56, the percentage of break even point is 42.23 % and the capacity of break even point is 66 892 sq ft.